A) x-(25% * x+25% * x+60)=20
b) 25% * x + 75% * x +9=x
c) 1/2 - 3/4 x - | ( 4x + 1 ) | 1 - x + 1 podzielić na 4
d ) 2/3( 3x - 1 )- 3/2 | 2x + 3(x-2) | = 1
e) 4x-3= 3x + 5
f) 5x + 2 = 7-3x
g) 3( x - 1 )= 0
h) -6(x + 1 ) = 24
i) -7 ( x -2 ) = 3x - 1
j) 4( x -1 )= 6( 1 + x )
k) 0,2 x + o,3 = - 0,7
l) 0,4 + 0,25 x = -2
ł) 2,1 - 0,3 = 0,4 x
m) -1,5x - 3= 0,2x + 6



PILNE. ; )

2

Odpowiedzi

  • Użytkownik Zadane
2010-04-05T13:59:10+02:00
A) x-(25% * x+25% * x+60)=20
x-(0,25x+0,25x+60)=20
x-(0,5x+60)=20
x-0,5x-60=20
0,5x-60=20
0,5x=80
x=160

b) 25% * x + 75% * x +9=x
0,25x+0,75x+9=x
x+9=x
9=0
sprzeczne

e) 4x-3= 3x + 5
x-3=5
x=8

f) 5x + 2 = 7-3x
8x+2=7
8x=5
x=⅝

g) 3( x - 1 )= 0
3x-3=0
3x=3
x=1

h) -6(x + 1 ) = 24
-6x-6=24
-6x=30
x=-5

i) -7 ( x -2 ) = 3x - 1
-7x+14=3x-1
-10x=-15
x=1,5

j) 4( x -1 )= 6( 1 + x )
4x-4=6+6x
-2x-4=6
-2x=10
x=-5

k) 0,2 x + o,3 = - 0,7
0,2x=-1
x=-5

l) 0,4 + 0,25 x = -2
0,25x=-2,4
x=-9,6

ł) 2,1 - 0,3 = 0,4 x
1,8=0,4x
x=4,5

m) -1,5x - 3= 0,2x + 6
-1,7x-3=6
-1,7x=9
-17x=90
x=-90/17
x=-5 i 5/17
  • dmai
  • Początkujący
2010-04-05T14:10:09+02:00
A) x-(25% * x+25% * x+60)=20
x-(0,25x+0,25x+60)=20
x-(0,5x+60)=20
x-0,5x-60=20
0,5x-60=20
0,5x=80
x=160

b) 25% * x + 75% * x +9=x
0,25x+0,75x+9=x
x+9=x
9=0
sprzeczność, brak rozwiązań
d) 2/3( 3x - 1 )- 3/2 | 2x + 3(x-2) | = 1
2x- 2/3 -3/2| 2x+ 3x- 6|= 1
2x- 2/3 - 3/2|5x -6|= 1
2x -2/3 - 15/2x +9= 1
- 5 1/2x = 1- 9+ 2/3 /( - 5 1/2)
x= - 1 1/3

e) 4x-3= 3x + 5
x-3=5
x=8

f) 5x + 2 = 7-3x
8x+2=7
8x=5
x=⅝

g) 3( x - 1 )= 0
3x-3=0
3x=3
x=1

h) -6(x + 1 ) = 24
-6x-6=24
-6x=30
x=-5

i) -7 ( x -2 ) = 3x - 1
-7x+14=3x-1
-10x=-15
x=1,5

j) 4( x -1 )= 6( 1 + x )
4x-4=6+6x
-2x-4=6
-2x=10
x=-5

k) 0,2 x + o,3 = - 0,7
0,2x=-1
x=-5

l) 0,4 + 0,25 x = -2
0,25x=-2,4
x=-9,6

ł) 2,1 - 0,3 = 0,4 x
1,8=0,4x
x=4,5

m) -1,5x - 3= 0,2x + 6
-1,7x-3=6
-1,7x=9
-17x=90
x=-90/17
x=-5 i 5/17